Problems of multiculturalism in the polish health care system - Bernaciak, Elżbieta; Farbicka, Paulina; Jaworska-Czerwińska, Aleksandra; Nartowicz, Małgorzata; Juraszek, Karolina Małgorzata (Journal of Education, Health and Sport, 2018)
Introduction: Medical staff in Poland increasingly take care of a person representing a different culture. Aim: To know nurses’ knowledge about the customs of people presenting different religions and cultural issues in modern health care. Method: The authoring three-part questionnaire was used to assess the knowledge of multiculturalism. Nonparametric tests were used for the comparison of variables: Kruskal-Wallis ANOVA and Wilcoxon pair order. Results: The overall level of knowledge of different cultures /religions was 8.00 for the whole study group. The highest level of knowledge among nurses was knowledge about Buddhism (1.00) and the lowest level about Hinduism (0.40). Conclusions: Most people did not have any lecture on multiculturalism in medicine during their education. The basic concepts of Judaism, Islam and Christianity are very well known. The knowledge of customs in different religions is small. Adaptation of multicultural education curricula in medical schools is an essential factor to ensure patients and their families appropriate conditions in the Polish health service. There was no conflict of interest.